The Analysis Of Hotel Room Cost Based on Activity Based Costing System at “RTS” Baturiti - L G R D Rahayu; I N Subratha; I W P Suta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
The purpose of this research to analyze and reveal the cost of hotel room based on Full Costing at Royal Tulip Saranam Resort & Spa (RTS) Baturiti, the cost of hotel room based on Activity Based Costing System (ABCS) at RTS Baturiti, and knowing the efficiency of the cost of hotel room based on ABCS at RTS Baturiti. The application of ABCS method at RTS Baturiti is expected to control costs better than to use of the Full Costing method in the hotel because the ABCS method allocates activity-based costs so as to provide a more accurate cost measurement of activity cost triggers. The result of the cost of hotel room by using ABCS, when compared with Full Costing method, it is seen that room type Saranam Room, Saranam Retreat, Deluxe Saranam, Saranam Deluxe Family, Saranam Suite shows the smaller difference from the stipulation of basic expenses in RTS Baturiti, show that for Saranam Room Rp 52.767, Saranam Retreat Rp 29.699, Saranam Deluxe Rp 328.263, Deluxe Family Saranam Rp 210.183 and Saranam Suite Rp 837.689. As for the type of room Hiltop Villa shows a larger difference around Rp 1.943.022. The difference is due to the cost of the cost driver in each room type. ABCS is able to allocate the cost of activity to each room type appropriately based on the consumption of each activity.